Analisis minat siswa dalam ekstrakulikuler futsal di SMP institut indonesia - kartika, dewi wulan; hadi, Hsnul; widiyatmoko, fajar ari (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
This study aimed to analyze the level of student interest in futsal extracurricular activities at SMP Institut Inonesia, specifically examining diffeences based on gender and across grade levels VII, VIII, and IX. Using a descriptive quantitative approach with a cross-sectional survey desaign, the research involved 214 students selected through random sampling from a total population of 459 students. Data were collected using a validated 20-item likert scale questionnaire and analyzed through descriptive statistics, the Chi-Square Test of Independence for gender comparison, and ANOVA for grade-level comparison. The results showed that students generally had a high level of interest in futsal extracurricular activities, with 73.4% indicating positive interest (57.5% high and 15.9% very high). A significant difference in interest was found between male and female students, with male students showing higher interest than female students. However, no significant differences were found among grade levels VII, VIII, and IX, indicating that students' interest in futsal extracurricular activities was relatively consistent across grade levels.